Biomechanical adaptations in the acceleration phase of bend sprinting. - Judson, L. J. (Sheffield Hallam University, 2019)
During bend sprinting athletes are unable to reach the same maximal speeds achieved on the straight. Since over half of the race distance is run on a curved portion of track, this has implications for race performance. This thesis aims to understand the biomechanical aspects of technique and performance in the acceleration phase of bend sprinting. Chapter 3: The accuracy of two reduced marker sets (lower limb and lower limb and trunk) were evaluated in comparison to a full-body marker set in the calculation of the centre of mass location and associated variables (velocity, touchdown distance and turn of centre of mass). Intraclass correlation coefficients demonstrated excellent agreement between all marker sets. However, the lower limb and trunk model was favoured and recommended for future use due to the marginally better agreement observed and the requirement for only four additional markers compared with the lower limb model. Chapter 4: The within- and between-day reliability of a lower limb and trunk marker set was established during bend sprinting. The results demonstrated that, where possible, data for each participant should be collected in the same session to increase reliability and reduce the required minimum detectable difference. The minimum detectable difference was used in subsequent studies to aid in the interpretation of results. Chapter 5: This marker set was used to identify the biomechanical adaptations of the lower limb during the acceleration phase of bend sprinting with a 36.5 m radius (lane one). Whilst the left limb demonstrated a greater peak hip adduction, peak hip internal rotation and peak ankle eversion on the bend compared with the straight, the right limb was characterised by an increase in peak hip abduction. In addition, with regard to spatio-temporal variables, there was a reduction in left step frequency and touchdown distance. Chapter 6: The use of statistical parametric mapping revealed a lower propulsive force at 38 - 44 % of stance on the bend than straight. In the left limb, this coincided with the use of the oblique axis for push-off at the metatarsophalangeal joint. In addition, mediolateral force was higher on the bend than the straight for the majority of the stance phase (3-96%). Chapter 7: No changes in extensor moment were observed at the hip and knee joints. Large effect sizes suggest a trend towards an increase in left step peak ankle plantar flexor moment. This increased plantar flexor moment may be due to a greater need for stabilisation as a consequence of non-sagittal plane adaptations of the lower limb.